2016
DOI: 10.1038/nmat4789
|View full text |Cite
|
Sign up to set email alerts
|

Collagen intrafibrillar mineralization as a result of the balance between osmotic equilibrium and electroneutrality

Abstract: Mineralisation of fibrillar collagen with biomimetic process-directing agents has enabled scientists to gain insight into the potential mechanisms involved in intrafibrillar mineralisation. Here, by using polycation- and polyanion-directed intrafibrillar mineralisation, we challenge the popular paradigm that electrostatic attraction is solely responsible for polyelectrolyte-directed intrafibrillar mineralisation. Because there is no difference when a polycationic or a polyanionic electrolyte is used to direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
191
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 243 publications
(211 citation statements)
references
References 44 publications
5
191
0
2
Order By: Relevance
“…Larger ACP granules were identified in the autolysosomes, probably because of the aggregation of fluidic ACP droplets derived from the degraded mitochondria. These droplets are liquid‐like and moldable prior to their transformation into crystalline CaP phases 1, 18. After their transfer to the extracellular milieu via exocytosis,3 the ACP droplets remained amorphous initially (Figure S2A, Supporting Information) and co‐existed with the unmineralized collagen fibrils (Figure S2B, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Larger ACP granules were identified in the autolysosomes, probably because of the aggregation of fluidic ACP droplets derived from the degraded mitochondria. These droplets are liquid‐like and moldable prior to their transformation into crystalline CaP phases 1, 18. After their transfer to the extracellular milieu via exocytosis,3 the ACP droplets remained amorphous initially (Figure S2A, Supporting Information) and co‐existed with the unmineralized collagen fibrils (Figure S2B, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Abnormality in this process results in highly morbid pathological conditions such as osteoporosis, osteoarthritis, osteogenesis imperfecta, or Paget's disease. Biomineralization is initiated via amorphous calcium phosphate (ACP) precursors that infiltrate the extracellular collagen matrix and subsequently transform into intrafibrillar carbonated apatite 1. The ACP precursor phase, in turn, is produced by coalescence of prenucleation clusters of hydrated calcium and phosphate ionic aggregates 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the presence of the highly charged polymer is vitally important to the successful oriented crystallization of apatite inside collagen fibrils. Charged polymers mimicking NMPs may make ACP precursors liquid-like (called polymer-induced liquid-like precursors, PILPs) [31] and highly-charged [110], or they may alter the osmotic pressure [111], which in the end facilitates ACP precursors to go inside collagen fibrils. Olstza et al reported that with the PILP process [31], ACP precursors can be infiltrated into collagen fibrils.…”
Section: Biomimetic Organic Matrixmentioning
confidence: 99%
“…Inspired by the effect of long-chain polyamines on stabilization of orthosilicic acid during biosilicification of silica-containing organisms, Niu et al have developed poly(allylamine)-stabilized ACP (PAH-ACP) for intrafibrillar mineralization of collagen. 32 However, it is not known whether this novel PILP phase remains effective for biomineralization following its loading, storage, and release from the pMSN. Accordingly, three hypotheses were tested in the present study: 1) positively charged PAH-ACP may be effectively loaded and released from nonfunctionalized pMSN; 2) PAH-ACP released from loaded pMSN still retains its ability to infiltrate and mineralize collagen fibrils; and 3) complete degradation of pMSN occurs following unloading of their PAH-ACP cargo.…”
mentioning
confidence: 99%